SINERGI KECERDASAN EMOSIONAL DAN MODERASI BERAGAMA SEBAGAI PILAR KOMPETENSI GLOBAL MASA DEPAN - Sandrina Ramadhani; Donna Takrim; Sri Juwita; Kasinyo Harto; Irja Putra Pratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the synergy between emotional intelligence and religious moderation as fundamental pillars in shaping future global competencies. The research employs a qualitative approach using the Systematic Literature Review (SLR) method, which involves identifying, selecting, and analyzing relevant academic literature. The findings indicate that emotional intelligence plays a crucial role in developing individuals’ ability to manage emotions, build empathy, and establish harmonious social relationships. Meanwhile, religious moderation serves as a value framework that emphasizes tolerance, balance, and respect for diversity. The synergy between these two aspects produces individuals who are not only capable of adapting to global dynamics but also able to uphold humanitarian values in social life. In the context of education, the integration of emotional intelligence and religious moderation has significant implications for character building and the development of students' global competencies. Therefore, strengthening these aspects is essential in addressing increasingly complex global challenges. This study is expected to provide a conceptual contribution to the development of character-based education and global competence.